A generative adversarial network‐based (GAN‐based) architecture for automatic fiducial marker detection in prostate MRI‐only radiotherapy simulation images. Issue 12 (19th October 2020) - Singhrao, Kamal; Fu, Jie; Parikh, Neil R.; Mikaeilian, Argin G.; Ruan, Dan; Kishan, Amar U.; Lewis, John H.
Abstract : Purpose: Clinical sites utilizing magnetic resonance imaging (MRI)‐only simulation for prostate radiotherapy planning typically use fiducial markers for pretreatment patient positioning and alignment. Fiducial markers appear as small signal voids in MRI images and are often difficult to discern. Existing clinical methods for fiducial marker localization require multiple MRI sequences and/or manual interaction and specialized expertise. In this study, we develop a robust method for automatic fiducial marker detection in prostate MRI simulation images and quantify the pretreatment alignment accuracy using automatically detected fiducial markers in MRI. Methods and Materials: In this study, a deep learning‐based algorithm was used to convert MRI images into labeled fiducial marker volumes. Seventy‐seven prostate cancer patients who received marker implantation prior to MRI and CT simulation imaging were selected for this study. Multiple‐Echo T1 ‐VIBE MRI images were acquired, and images were stratified (at the patient level) based on the presence of intraprostatic calcifications. Ground truth (GT) contours were defined by an expert on MRI using CT images. Training was done using the pix2pix generative adversarial network (GAN) image‐to‐image translation package and model testing was done using fivefold cross validation. For performance comparison, an experienced medical dosimetrist and a medical physicist each manually contoured fiducial markers in MRI images. The percent of correct detections and F1 classification scores are reported for markers detected using the automatic detection algorithm and human observers. The patient positioning errors were quantified by calculating the target registration errors (TREs) from fiducial marker driven rigid registration between MRI and CBCT images. Target registration errors were quantified for fiducial marker contours defined on MRI by the automatic detection algorithm and the two expert human observers. Results: Ninety‐six percent of implanted fiducial markers were correctly identified using the automatic detection algorithm. Two expert raters correctly identified 97% and 96% of fiducial markers, respectively. The F1 classification score was 0.68, 0.75, and 0.72 for the automatic detection algorithm and two human raters, respectively. The main source of false discoveries was intraprostatic calcifications. The mean TRE differences between alignments from automatic detection algorithm and human detected markers and GT were <1 mm. Conclusions: We have developed a deep learning‐based approach to automatically detect fiducial markers in MRI‐only simulation images in a clinically representative patient cohort. The automatic detection algorithm‐predicted markers can allow for patient setup with similar accuracy to independent human observers.